Integrated Study of the Dinitrobenzene Electroreduction Mechanism by Electroanalytical and Computational Methods - Andrey S. Mendkovich; Mikhail A. Syroeshkin; Ludmila V. Mikhalchenko; Mikhail N. Mikhailov; Alexander I. Rusakov; Vadim P. Gul'tyai (International Journal of Electrochemistry)
Electroreduction of 1,2-, 1,3-, and 1,4-dinitrobenzenes in DMF has been investigated by a set of experimental (cyclic voltammetry, chronoamperometry, and controlled potential electrolysis) and theoretical methods (digital simulation and quantum chemical calculations). The transformation of only one nitro group is observed in the presence of proton donors. The process selectivity is provided by reactions of radical anions' intermediate products. The key reactions here are protonation of radical anions of nitrosonitrobenzenes and N-O bond cleavage in radical anions of N-(nitrophenyl)-hydroxylamines.